Functional Hemodynamic Monitoring - Pinsky, Michael R.; Payen, Didier (Update in Intensive Care Medicine, 2005)
Hemodynamic monitoring is one of the major diagnostic tools available in the acute care setting to diagnose cardiovascular insufficiency and monitor changes over time in response to interventions. However, the rationale and efficacy of hemodynamic monitoring to affect outcome has come into question. We now have increasing evidence that outcome from critical illness can be improved by focused resuscitation based on existing hemodynamic monitoring, whereas non-specific aggressive resuscitation impairs survival. Thus, this book frames hemodynamic monitoring into a functional perspective wherein hemodynamic variables and physiology interact to derive performance and physiological reserve estimates that themselves drive treatment. This philosophy, as well as the limitations and applications of common and evolving hemodynamic measures and their focused use in the care of critically ill patients are discussed, relevant to one underlying truth: No monitoring device, no matter how simple or sophisticated, will improve patient-centered outcomes useless coupled to a treatment which, itself, improves outcome.